On statistical distributions of wide binary stars - Chulkov, D.A.; Trushin, D.I. (Advances in Astronomy and Space Physics, 2012)
The semi-major axis is a key parameter of binary stellar systems. In order to obtain current semi-major axis distribution we investigated a volume-limited sample of the binaries in solar neighbourhood. Obtained distribution shows unsatisfactory agreement with the canonical Opik's law.